INOVASI PENINGKATAN EFISIENSI PANEL SURYA BERBASIS FRESNEL SOLAR CONCENTRATOR DAN SOLAR TRACKER - Saputra, Muhammad Adhijaya; Azis, Muhammad Fadli (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Indonesia is a tropical country with great potential for solar energy is about 4.5 kWh per m2. However, this potential can not be fully utilized due to the efficiency of solar panels is still very low at around 16%. Various research and development of solar panels has been done in order to get a system with higher efficiency. Starting from the development of constituent materials, the selection of topology until the latest is the change construction design of the solar panels. That is a change from fixed solar panel model (fixed solar panels) into a solar tracker. With the discovery of the suns solar panels followers, efficiency solar panels can now be increased up to 16.5%. However, the figure is too low if the solar panel want to be a solar panel power generation technologies that can be utilized by the general public. We tried to develop a solar panel system by utilizing the Fresnel lens that can concentrate sunlight intensity on the solar cell. Then, because of the position of the sun that always changes, we use a solar tracker that automatically adjust the position of the solar panels to always face the sun. So with the combination of the two technologies, solar panel can absorb maximum sunlight intensity.Keywords:Solar Panels, Solar Tracker, Fresnel Solar Concentration.